Women and Couchsurfing: Empowerment and the Construction of Hybrid Identities in a Local-Global Context - Paquet, Jonathan (My University, 2013)
Couchsurfing is a worldwide virtual hospitality network. Conceived and launched more than a decade ago, the network firstly attracted people with financial capacities to travel, mainly from Western and more culturally liberal countries. Today, the community has extended to include people that may never travel abroad for cultural or financial hindrances, but who still can participate in a truly global network where like-minded foreigners and also locals gather, exchange and learn from each other. As a global web-based community of people aiming to meet in real life, Couchsurfing precipitates the intercultural encounters towards a rapid, proximate and useful experience for its members. These encounters may take place in more conservative societies where the act of hosting strangers and walking with foreigners may interfere with culturally embedded meanings, practices and limits. Especially when these encounters happen between genders. This research explores the Couchsurfing experiences of women coming from highly gender unequal societies, where travelling and hosting strangers may have immediate and future implications. Using Skype, semi-structured interviews were conducted to collect the stories of these women. Using Grounded Theory, this qualitative research shows that women can use Couchsurfing as a tool to construct their hybrid identity, gain social, cultural and symbolic capital, and that Couchsurfing creates “spaces” where women can empower themselves and experience new gender dynamics.
Keywords: Couchsurfing; women empowerment; globalization; global and local; hybrid identity; gender in intercultural encounters; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|